(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In simplest terms, the HR (Human Resources) department is a group who is responsible for managing the employee life cycle (i.e., recruiting, hiring, onboarding, training, and firing employees) and administering employee benefits.